Pentingnya Manajemen Isu bagi Maskapai Penerbangan dalam Menghadapi Dampak COVID-19 (Studi: Cathay Pacific Airways) - Levana, Emerentia; Harnadi, Agnes; Kusumawicitra, Astuti (School of Communication - Atma Jaya Catholic University of Indonesia, 2021)
Unplanned events are unexpected and are often referred to as “negative shocks” in the world of tourism. One of the example is an outbreak or a pandemic. When it occurred, one of the tourism sectors that is most affected is airlines. Since the World Health Organization (WHO) declared the pandemic on March 2020, the airlines industry, including Cathay Pacific are experiencing a significant decline because of some restrictions such as lockdown, tourist attractions closed, flights canceled and social distancing. This study was conducted on March-December 2020. The main aim of the study is to examine the steps that Cathay Pacific Airways has taken according to issue management in overcoming the impact of the COVID-19 pandemic. The qualitative reseach method is used with data collection based on interviews with staff of Cathay Pacific Airways representative office in Indonesia, direct observation, and secondary data from supporting documents. The results obtained from this study is that Cathay Pacific Airways can handle the issue by launching Cathay Care Campaign, Cathay Credit and Fly Worry Free. The airlines also followed the stages of issue lifecycle. Through this program, Cathay Pacific Airways is also able to maintain trust and convince the guests (or prospective passangers). Those capabilities can be seen from the operational activities that are still ongoing even though route cuts and departure cancellations often have to be carried out.